NEWSPAPERS “RUSYN” (1920-1923), “RUS’KA MOVA” (1920-1924) AND THE FORMATION OF CONSCIOUSNESS OF ZAKARPATTIA’S DWELLERS - Dobosh, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The research is conducted on the periodicals of Zakarpattia in the 20s of the previous century, namely Ukrainian newspapers “Rusyn”, “Rus’ka mova”, “Ukrains’ke slovo” and others. It proves that their bright pro-Ukrainian position promoted the national renaissance of the land’s dwellers – awoke a feeling of patriotism, human dignity in them. The author meticulously analyses the content of such editions from modern positions, their role in the development of other pro-Ukrainian newspapers and periodicals.